Role of Fungi in Weathering of Teak Fruits - Dadwal, V. S.; , Jamaluddin (Indian Forester, 1988)
A wide variety of fungal flora is involved during the process of natural weathering of teak fruit. Scytalidium sp. exhibited fast decomposition of epicarp from the fruit which resulted the completion of weathering of teak fruits within 21 days. The seeds extracted from such weathered lot through use of Scytalidium sp. exhibited high percentage of germination as compared with the other treatments. It is recommended that Scytalidium sp. can be used for fast weatherlng of teak fruits.